THE IMPACT OF ISLAMIC FINANCE TOWARDS HALAL PRODUCT DEVELOPMENT AND PATRONISING HALAL SMES IN NIGERIA - Muhammad, Tijjani; Yakasai, Musa Umar (International Journal of Islamic Business & Management, 2022)
The study assesses the level of Islamic finance on halal awareness, products, certification, and brands through the behavioural intention to patronise Islamic SMEs products for better Halal production, as most of the SME’s products neglect Halal certification in their daily production. Design/Methodology/Approach: The study used the Confirmatory Factor Analysis under Structural Equation modelling using a qualitative data collection technique through convenience sampling. The cluster sampling of selecting the SMEs with their consumer. The validity and reliability were also tested for data justification. This paper designed and collected data from the three categories of stakeholders, Consumers and others in Northern Nigeria, considering the vast population of the states in the Northern part of the country. The result shows that the priority issues that enhanced social awareness, halal products, certification and halal brands have a positive relationship with market patronage. Further, describes the weak factors hindering halal certification through a cluster model based on the categories of the responses proposed by the halal integrity network. The practical implication addressed and developed an alternative way of managing factors that hamper the concerned Halal certification towards Halal industries and their ingredients and logistics for Muslim markets patronage. Originality/Value: It is challenging to find a paper that discusses factors that hamper Halal certification in Northern Nigeria and with a new method introduced of using CFA under SEM for model development industries in Northern Nigeria. JEL Classification Codes: D21, G19, M31.